ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT ANGGOTA KEPOLISIAN UNTUK MENABUNG DI BANK SYARIAH (Studi Pada Markas Kepolisian Resor Bogor Sektor Gunung Putri) - Zenal Mustakim; Tubagus Rifqy Thantawi; Azizah Mursyidah (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2021)
ABSTRACT The existence of the police is very closely related to society. Seeing that some people, including the police, still think that saving in Islamic banks and conventional banks is the same, due to the lack of socialization and public education to provide knowledge and understanding to the community, so that people know about the concepts, mechanisms, products, in terms of Islamic banking so they have the right information. Enough about Islamic banking financial institutions. The research method used in this study is field research (Field Research) with quantitative methods, namely the data obtained in the form of numbers that are calculated related to the problem under study. Service variables, Islamic banking products and religiosity together have a positive and significant effect on the interest of Polri members to save in Islamic banks. This is obtained from the tcount value of each variable and the F test results of 148.703 and the coefficient of determination (R2) of 0.925. The results that the author has done show that service factors, Islamic banking products and religiosity influence the interest of members of the Gunung Putri Bogor Police to save at Islamic banks. The factor that is more dominant in influencing the interest of Polri members is service.